2012
DOI: 10.1016/j.jmii.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and treatment outcomes of patients with tubo-ovarian abscess at a tertiary care hospital in Northern Taiwan

Abstract: Patients with TOA who underwent surgery had a longer duration of hospitalization. Among the patients who underwent surgical intervention, those admitted to the emergency room had higher CRP levels and were more likely to be multiparous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
4
14
2
Order By: Relevance
“…Our data also indicate an association rate of 59%, which is compatible with that reported in the literature. Previous studies reported that the prolonged duration of hospitalization was required in patients with TOA who underwent drainage or surgery (12,13,17). Similarly, we found that the mean duration of hospitalization was significantly longer in patients who were surgically treated.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our data also indicate an association rate of 59%, which is compatible with that reported in the literature. Previous studies reported that the prolonged duration of hospitalization was required in patients with TOA who underwent drainage or surgery (12,13,17). Similarly, we found that the mean duration of hospitalization was significantly longer in patients who were surgically treated.…”
Section: Discussionsupporting
confidence: 78%
“…In a study, a higher CRP level was identified as an important indicator for surgery. However, the lymphocyte and WBC counts in the same study were not significantly elevated (17). Güngördük et al (18) showed that CRP and ESR levels were higher in surgically treated patients.…”
Section: Discussionmentioning
confidence: 72%
“…6,7 In the present study, 46% patients had undergone a surgery within six months and 30% patients had undergone a surgery over six months before TOA development, which was consistent with that reported in previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported leukocyte counts and CRP levels of 11.500-16.000/mm 3 and 7.6-14 mg/dL, respectively, in patients undergoing medical treatment, and 14000-16700/mm 3 and 16.1-53.8 mg/dL, respectively, in patients undergoing surgical treatment, indicating that leukocyte counts and CRP levels of patients undergoing surgical treatment were higher than those of patients undergoing medical treatment. 7,12,[14][15][16] In the present study, the mean leukocyte count and CRP level of patients undergoing medical treatment were 11.850/mm 3 and 11.1 mg/dL, respectively, while those of patients undergoing surgical treatment were 13.780/mm 3 and 14.1 mg/dL, respectively, and those of patients undergoing USG-guided drainage were 14.870/mm 3 and 16.2 mg/dL, respectively. These findings indicated that leucocyte counts and CRP levels of patients undergoing surgical treatment were higher than those of patients undergoing medical treatment, which was consistent with that reported in previ- ous studies.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation